2016
DOI: 10.1021/acs.biomac.6b00316
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Properties of Core–Shell-Structured, Hemicellulose-Rich Nanofibrillated Cellulose in Dispersion and Wet-Film States

Abstract: We report the viscoelastic properties of core-shell-structured, hemicellulose-rich nanofibrillated cellulose (NFC) in dispersion and wet-film states. The hemicellulose-rich NFC (hemicellulose neutral sugars 23%, carboxylate 0.2 mmol g(-1)), prepared from Japanese persimmons, had a core crystallite thickness of 2.3 nm and unit fibril thickness of 4.2 nm. A carboxylate-rich NFC (hemicellulose neutral sugars 7%, carboxylate 0.9 mmol g(-1)) with crystallite and fibril widths of 2.5 and 3.3 nm, respectively, was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 65 publications
4
45
0
Order By: Relevance
“…2b), providing confidence that, even at the highest DS and DO values tested, film strength was not compromised. It was postulated that the strengthening of the modified films was due to increased density of packed fibrils within the films, as the modified films exhibited thickness of only 60-80% that of unmodified films, reflecting previous reports that films made from modified cellulose fibrils possess higher tensile strengths than native cellulose (Tanaka et al 2016). …”
Section: Mechanical Propertiessupporting
confidence: 57%
“…2b), providing confidence that, even at the highest DS and DO values tested, film strength was not compromised. It was postulated that the strengthening of the modified films was due to increased density of packed fibrils within the films, as the modified films exhibited thickness of only 60-80% that of unmodified films, reflecting previous reports that films made from modified cellulose fibrils possess higher tensile strengths than native cellulose (Tanaka et al 2016). …”
Section: Mechanical Propertiessupporting
confidence: 57%
“…Previous work has shown that aqueous dispersions of slender and kinked CNFs display non-Newtonian rheological behavior characterized by shear thinning and pronounced viscoelastic behavior at concentrations above the gelation threshold (de Kort et al 2016;Jowkarderis and van de Ven 2015;Martoia et al 2016). Recent studies have investigated the effects of pulp source (Tanaka et al 2016), fibril dimension and concentration (Agoda-Tandjawa et al 2010), mechanical treatments (Pääkkö et al 2007), ionic strength (Dong et al 2013), pH (Fall et al 2013), as well as addition of amphiphilic molecules (Quennouz et al 2016) on the rheology of CNF dispersions. Additionally, CNFs can also assist in preparation of homogeneous dispersions of a variety of fillers and pigments, such as carbon nanotubes (Hamedi et al 2014), reduced graphene oxide (Duan et al 2016), TiO 2 (Schütz et al 2012), and CaCO 3 (Lourenço et al 2016) nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…However, the gel strength can be controlled by adding salts in order to change the ionic strength. By increasing the ionic strength, stronger CNF networks are obtained due to screening of electrostatic interactions 39,41,58,59. At the same time, however, this leads to higher CNF aggregation and lower colloidal stability.…”
mentioning
confidence: 99%
“…At the same time, however, this leads to higher CNF aggregation and lower colloidal stability. The presence of charged polymers, e.g., hemicellulose, contributes also to the electrostatic interactions of CNFs and influences the rheological behavior 59. …”
mentioning
confidence: 99%